Computational analysis of the distribution of occlusal overloads exerted on zirconia implants (Research, Society and Development, 2022)
From the finite element analysis, the objective of the study was to evaluate the effectiveness of the occlusal splint against the overload of tensions and deformations exerted on zirconia implants. Occlusal loadings were performed at 300 N intensity, at 45º and 90º, with or without the use of an occlusal splint. The groups were divided into: cP/cV – with occlusal splint and vertical load; cP/cO – with occlusal splint and oblique loading; sP/cV – without occlusal splint and vertical load; sP/cO – without occlusal splint and oblique loading. For total deformation, the control groups showed evenly distributed stresses (~0.05 mm in cP/cO and ~0.008 mm in cP/cV), while for the groups without splint, the highest stress was observed in sP/cO. The maximum main implant and bone stress values, respectively, were higher for sP/cO (119 MPa and ~49 MPa) compared to the others (cP/cV 16 MPa and ~4 MPa; cP/cO 20 MPa and ~2, 5 MPa; sP/cV 16 MPa, and ~3.9 MPa). As for the minimum main implant and bone tensions, the highest values were for sP/cO (~32 MPa and ~61 MPa) when compared to the others (cP/cV ~4.6 MPa and ~18 MPa; cP/cO 3 MPa and ~10 MPa; sP/cV ~3.2 MPa, and ~18 MPa). The occlusal splint was effective for better stress distribution on the zirconia implant. The vertical load standardized the direction of voltages in the sP/cV group, promoting similar results to the control groups cP/cV and cP/CO. The sP/cO group presented the worst, with high values of heterogeneously distributed results.